A PRELIMINARY STUDY OF ASSOCIATION BETWEEN STRIATAL DOPAMINE FUNCTION, MENTALIZATION AND VISUAL MOTOR COORDINATION IN HEALTH AND FIRST EPISODE SCHIZOPHRENIA (FES): A SINGLE-PHOTON EMISSION COMPUTED TOMOGRAPHY (SPECT) STUDY USING [99MTC] TRODAT-1 - *Pin-Yen Lu; Yu-Lien Huang; Kao-Chin Chen; Po-See Chen; Yen-Kuang Yang; Huai-Hsuan Tseng (International Journal of Neuropsychopharmacology, 2025)
Abstract Background Patients with Schizophrenia have difficulties in social cognition, which were associated with sensory- motor function in a previous study. The aberrancy of the striatum and the dopaminergic system has been reported as contributing to social and sensor motor dysfunction in schizophrenia. Nevertheless, the integrated exploration of the striatal dopamine function, mentalization, and sensorimotor aspects, particularly in early disease stages, remains underexplored. Aims & Objectives The striatum is a subcortical nucleus receiving dopaminergic inputs, with the subdivision of the putamen playing a role in motor skills and the caudate involved in motor and cognitive function. With deceleration in the information, sensory-motor dysfunction might lead to mentalization deficits. We hypothesized due to dopaminergic system dysregulation in the striatum, first episode schizophrenia (FES) would have mentalization (caudate-related) and visual-motor coordination (putamen-related) impairment. Method We recruited FES over 5 years and healthy individuals with screening of The Mini-International Neuropsychiatric Interview (M.I.N.I.) by psychiatrists. All Participants received the Movie for the Assessment of Social Cognition-Taiwanese version (MASC-TW), a 15-minute video of social situations with four response options: correct, overmentalizing, undermentalizing, and no-mentalizing. They completed a visual-motor coordination task, using the joystick to track the round dots displayed on the screen. The striatal dopamine transporter (DAT) availability was assessed in both groups by single- photon emission computed tomography (SPECT) using [99mTc] TRODAT-1. Correlational analyses and a linear regression model between mentalization, visual motor coordination, and DAT availability were explored. Results We enrolled 16 FES (10 males, 6 females) and 43 healthy controls (38 males, 5 females). Both groups had similar mean ages (schizophrenia 30.13 ± 9.33). Education years varied significantly between the two groups (t = -2.94, p = 0.003). These patients were clinically stable (CGI =3.73 ± 1.10). FES showed significantly worse MASC-correct (t= − 3.26, p=0.001) and joystick score (t= − 3.30, p=0.001) than healthy individuals. In healthy individuals, MASC-cognition and initial joystick performance were significantly correlated (r=0.341, p=0.031). There was a negative association between MASC- overmentalizing and the DAT availability at left caudate nucleus (r= − 0.349, p=0.027). In FES, joystick learning capacity was notably associated with the DAT availability at left striatum (r=0.536, p=0.040), particularly the left putamen (r=0.458, p=0.087). Discussion & Conclusion We explored the associations between striatal DAT availability, mentalization, and visual-motor coordination in FES and in healthy individuals. Mentalization was associated with sensory-motor function. Furthermore, evidence showed the potential of the DAT availability at left caudate and left putamen to contribute to mentalization and visual-motor coordination, respectively. Our findings supported social cognition deficits attributed to early-stage striatal changes. They aligned with prior research that reduced left putamen volume and weaker left caudate specialization in schizophrenia and early cortico-striatal hypoconnectivity in FES. Further study is warranted to confirm the observation with a larger population. References 1.Yang YK, Chiu NT, Chen CC, Chen M, Yeh TL, Lee IH. Correlation between fine motor activity and striatal dopamine D2 receptor density in patients with schizophrenia and healthy controls. Psychiatry Res. 2003 Jul 30;123(3):191-7. doi: 10.1016/s0925-4927(03)00066-0. PMID: 12928107. 2.Chen PS, Jamil A, Liu LC, Wei SY, Tseng HH, Nitsche MA, Kuo MF. Nonlinear Effects of Dopamine D1 Receptor Activation on Visuomotor Coordination Task Performance. Cereb Cortex. 2020 Sep 3;30(10):5346-5355. doi: 10.1093/cercor/bhaa116. PMID: 32483622. 3.Lu PY, Huang YL, Huang PC, Liu YC, Wei SY, Hsu WY, Chen KC, Chen PS, Wu WC, Yang YK, Tseng HH. Association of visual motor processing and social cognition in schizophrenia. NPJ Schizophr. 2021 Apr 13;7(1):21. doi: 10.1038/s41537-021-00150-7. PMID: 33850147; PMCID: PMC8044174. 4.Huang YL, Chen TT, Dziobek I, Tseng HH. Mentalizing in a movie for the assessment of social cognition (MASC): the validation in a taiwanese sample. BMC Psychol. 2023 Sep 22;11(1):287. doi: 10.1186/s40359-023-01321-0. PMID: 37740240; PMCID: PMC10517527. 5.Huang X, Pu W, Li X, Greenshaw AJ, Dursun SM, Xue Z, Liu H, Liu Z. Decreased Left Putamen and Thalamus Volume Correlates with Delusions in First-Episode Schizophrenia Patients. Front Psychiatry. 2017 Nov 20;8:245. doi: 10.3389/fpsyt.2017.00245. PMID: 29209237; PMCID: PMC5702009. 6.Mueller S, Wang D, Pan R, Holt DJ, Liu H. Abnormalities in hemispheric specialization of caudate nucleus connectivity in schizophrenia. JAMA Psychiatry. 2015 Jun;72(6):552-60. doi: 10.1001/jamapsychiatry.2014.3176. PMID: 25830688; PMCID: PMC463021 7.Nelson EA, Kraguljac NV, Maximo JO, Armstrong W, Lahti AC. Dorsal striatial hypoconnectivity predicts antipsychotic medication treatment response in first-episode psychosis and unmedicated patients with schizophrenia. Brain Behav. 2022 Nov;12(11):e2625. doi: 10.1002/brb3.2625. Epub 2022 Oct 13. PMID: 36237115; PMCID: PMC9660417. 8.Sarpal DK, Robinson DG, Lencz T, Argyelan M, Ikuta T, Karlsgodt K, Gallego JA, Kane JM, Szeszko PR, Malhotra AK. Antipsychotic treatment and functional connectivity of the striatum in first-episode schizophrenia. JAMA Psychiatry. 2015 Jan;72(1):5-13. doi: 10.1001/jamapsychiatry.2014.1734. PMID: 25372846; PMCID: PMC4286512.